Senator Will Lee: Mounting Fears - Book 7 - Woods, Stuart (New York : Signet, 2009)
In the aftermath of the vice presidents unexpected death, President Will Lee finds his efforts to select a replacement hampered by a contenders secret misdeeds, a rogue CIA agents vengeful plot against the first lady, and a nuclear threat in Pakistan.
"A Signet book"--T.p.
Keywords: Lee, Will (Fictitious character) -- Fiction; Barker, Holly (Fictitious character) -- Fiction; Presidents -- Election; Fiction; Intelligence officers -- Fiction; Nuclear warfare -- Fiction; Conspiracies -- Fiction; Washington (D.C.) -- Fiction; Political fiction; Thrillers (Fiction)